Theatrical Release Windows: A Playground for “Cultural Exception” Policies? (Cinéma & Cie. Film and Media Studies Journal, 2024)
In recent years, cinema culture in Europe has undergone a substantial reorganization of production models and a profound change of public intervention in favor of the film industry. This article aims to reconstruct the different combinations between protectionist and liberalist policies through a comparative analysis of the contemporary European national cinema aids, identifying differences and shared trends and verifying the existence of a “continental” cinema support model. Therefore the article will analyze public support policies on cinema production, distribution, and exhibition in the EU and in several of its member states (including France, Germany, England, Spain, and Italy) from 2018 to 2022. Focusing on theatrical release windows, this essay will attempt to answer the following main questions: is there a “European” mark in policies in favor of cinema? Can we speak of a “European” model (even outside the European Union) of support for the cinema? What are the elements and actions that define it? What are the sectors of the industry in which it is most fully expressed (production, distribution, exhibition)? And what are the themes and areas in which, on the contrary, national differences (sometimes driven by resurgent nationalisms) are most marked?
Keywords: Public Cinema Funding; Release Windows; Nationalism; Pandemic Crisis; Cultural Exception